0256 Can a Single Night's Sleep Architecture Predict Next-Day Affect and Affect Regulation?. (27th May 2020) - ten Brink, M; Zhang, J; Manber, R; Kreibig, S; Gross, J J
Abstract: Introduction: Disrupted sleep has been shown to alter next-day affective functioning by decreasing positive mood, increase negative reactivity, and impairing people's ability to regulate their affect. However, few studies have examined how particular aspects of sleep timing and architecture influence typical daytime affect. Based on clinical and laboratory research on reactivity to emotional stimuli, we hypothesized a particularly important role for REM sleep in next-day affective functioning. Methods: We analyzed a subset of N = 64 from a larger study of healthy adult community members who had complete data from a single night of ambulatory polysomnography (PSG) at home as well as morning and evening diaries. We tested whether PSG-derived total sleep time, sleep efficiency, REM percentage, REM latency, and SWS latency predicted self-reported negative mood and use of affect regulation the following morning and day using linear regression models. Results: Surprisingly, there were no significant associations (p > 0.05) between any of the five PSG sleep architecture measures with self-reported negative morning mood, daytime mood, or daytime affective regulation. Conclusion: This finding indicates that objective sleep measures from a single night of at home PSG in a healthy adult population are not necessarily predictive of an individual's subsequent emotional well-being on the following day. Support: National Science Foundation Graduate Fellowship